1990
DOI: 10.1073/pnas.87.18.7220
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the T-cell antigen receptor: evidence for two CD3 epsilon subunits in the T-cell receptor-CD3 complex.

Abstract: The T-cell antigen receptor (TCR) consists of heterodimeric glycoproteins (TCR a,4 or yS) that demonstrate homology with immunoglobulins. Noncovalently associated with the afi (or y8) heterodimer are at least five nonvariant proteins (CD3-y, -8, -e, -j, and -ig), which together comprise the TCR-CD3 complex. The stoichiometry of the antigen receptor has been assumed to be either apyBvSiCor a(y8e{7g.In this paper we provide several lines of evidence that support the notion that the mature TCR-CD3 complex on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 20 publications
(13 reference statements)
5
59
0
1
Order By: Relevance
“…The results indicated that a TCR -TCR heterodimer binds a single CD3 -CD3 heterodimer, a single CD3 -CD3 heterodimer and a CD3 -CD3 homodimer. Thus, the overall stoichiometry of the TCR complex was found to be 1:1:1:1:2:2 (for TCR, TCR, CD3 , CD3 , CD3 , and CD3 , respectively) (Rudolph et al, 2006;Wucherpfennig et al, 2010) These findings corroborated the stoichiometry proposed in a previous study (Blumberg et al, 1990), and are supported by other results, as well (Call et al, 2004). However, other works suggested that a second heterodimer was incorporated into the complex, suggesting an ( ) 2 stoichiometry (Exley et al, 1995;Fernandez-Miguel et al, 1999;San Jose et al, 1998).…”
Section: Current Understanding Of Stoichiometry Of the Complexes Invosupporting
confidence: 89%
“…The results indicated that a TCR -TCR heterodimer binds a single CD3 -CD3 heterodimer, a single CD3 -CD3 heterodimer and a CD3 -CD3 homodimer. Thus, the overall stoichiometry of the TCR complex was found to be 1:1:1:1:2:2 (for TCR, TCR, CD3 , CD3 , CD3 , and CD3 , respectively) (Rudolph et al, 2006;Wucherpfennig et al, 2010) These findings corroborated the stoichiometry proposed in a previous study (Blumberg et al, 1990), and are supported by other results, as well (Call et al, 2004). However, other works suggested that a second heterodimer was incorporated into the complex, suggesting an ( ) 2 stoichiometry (Exley et al, 1995;Fernandez-Miguel et al, 1999;San Jose et al, 1998).…”
Section: Current Understanding Of Stoichiometry Of the Complexes Invosupporting
confidence: 89%
“…On ligand binding by the TCR, cytoplasmic ITAM motifs in the CD3 and z chains become phosphorylated by the Src-family kinase Lck (Weiss and Littman 1994), constituting the earliest detectable biochemical consequence of TCR ligation. Early genetic, biochemical, and immunofluorescencebased experiments established that the intact TCR-CD3 complex contains two copies of CD31 (Blumberg et al 1990b;de la Hera et al 1991), consistent with a model in which both CD3d1 and CD3g1 are incorporated into each abTCR complex. Similar approaches have failed to detect more than one TCRa or TCRb chain in intact TCR-CD3 complexes (Punt et al 1994;Call et al 2002), indicating that the receptor is monovalent with respect to the ligand-binding module.…”
Section: Tcr-cd3 Stoichiometrymentioning
confidence: 94%
“…The remaining subunits, termed CD3-y, -ö, -E, -~, and -1], are invariant, noncovalently associated with the TCR aß dimer, and possess large intracytoplasmic domains thought to be responsible for coupling antigen recognition to various signal transductlon pathways. The evolutionarily related y, Ö, and e subunits are expressed as noncovalently associated ye and OE pairs (Koning et al, 1990;Blumberg et al , 1990;De la Herra et al , 1991), and display immunoglobulin-like extracellular domains (Gold et al, 1987). In contrast, the ~ and 1] subunlts contaln an extracellular domain of only 9 residues and constitute the prototype of a new protein family that includes the y chain of the high affinity IgE receptor (FceRI) (Weissmanetal., 1988;Jinetal., 1990;Küsteretal., 1990).…”
Section: Introduetionmentioning
confidence: 99%